To solve ax2 + bx + c = 0 by completing the square:
1. Transform the equation so that the constant term, c, is alone on the right side.
2. If a, the leading coefficient (the coefficient of the x2 term), is not equal to 1, divide both sides by a.
3. Add the square of half the coefficient of the x-term, to both sides of the equation.
4. Factor the left side as the square of a binomial.
5. Take the square root of both sides. (Remember: (x + q)2 = r is equivalent to .
6. Solve for x.
Solve x2– 6x – 3 = 0 by completing the square.
Solve: 7x2– 8x + 3 = 0